Food transfers, cash transfers, behavior change communication and child nutrition: Evidence from Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini (International Food Policy Research Institute, 2019)
The importance of children’s nutritional status for subsequent human capital formation, the limited evidence of the effectiveness of social protection interventions on child nutrition, and the absence of knowledge on the intra-household impacts of cash and food transfers or how they are shaped by complementary programming motivate this paper. We implemented two, linked randomized control trials in rural Bangladesh, with treatment arms including cash transfers, a food ration, or a mixed food and cash transfer, as well as treatments where cash and nutrition behavior change communication (BCC) or where food and nutrition BCC were provided. Only cash plus nutrition BCC had a significant impact on nutritional status, but its effect on height-for-age z scores (HAZ) was large, 0.25SD. We explore the mechanisms underlying this impact. Improved diets – including increased intake of animal source foods – along with reductions in illness in the cash plus BCC treatment arm are consistent with the improvement we observe in children’s HAZ.